Trade liberalization and the evolution of skill earnings differentials in Brazil - Gustavo Gonzaga; Naércio Menezes Filho; Cristina Terra (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2002)
From 1988 to 1995, when trade liberalization was implemented in Brazil, relative earnings of skilled workers decreased. In this paper, we in-vestigate the role of trade liberalization in explaining these relative earn-ings movements, by checking all the steps predicted by the Heckscher-Ohlin- style trade transmission mechanism. We find that: i) employment shifted from skilled to unskilled intensive sectors, and each sector increased its relative share of skilled labor; ii) relative prices fell in skill intensive sectors; iii) tari .changes across sectors were not related to skill inten-sities, but the pass-through from tari .s to prices was stronger in skill intensive sectors; iv) the decline in skilled earnings di .erentials mandated by the price variation predicted by trade is very close to the observed one. The results are compatible with trade liberalization, accounting for the observed relative earnings changes in Brazil.
Keywords: F13; J31; 330; earnings inequality; trade liberalization; Handelsliberalisierung; Faktorproportionentheorem; Qualifikation; Lohn; Brasilien